Atomic Habits: Metode Transformasi diri - Susi Susilawati; Masduki Asbari; Denisse Pratiwi; Fani Putri Amaliya; Riza Rahmawati; Saufitri Komalasari (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this study is to present a book review with a critical reading of the title Atomic Habits by James Clear. The descriptive qualitative research method was used to analyze the content of the book. The findings of the study show that this book provides valuable insights into the importance of small habits in achieving significant life changes, describes clearly and in detail, the mechanisms of habit formation and the strategies that can be used to form successful habits, highlights the role of the environment in habit formation and provides practical guidance on how to create an environment that supports positive habit change.